2016
DOI: 10.1074/jbc.m115.681833
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Adenine Dinucleotide Phosphate Plays a Critical Role in Naive and Effector Murine T Cells but Not Natural Regulatory T Cells

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP), the most potent Ca 2؉ mobilizing second messenger discovered to date, has been implicated in Ca 2؉ signaling in some lymphomas and T cell clones. In contrast, the role of NAADP in Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…6 A) results from TPC pore blocking ability. Our data also suggest caution in attribution of the mechanistic basis of effects of SKF96365 in studies of Ca 2+ signaling [ 70 ]. PF-543 is a cell-permeant inhibitor of sphingosine kinase [ 49 ], application of which causes a dose-dependent increases in cellular sphingosine levels.…”
Section: Discussionmentioning
confidence: 94%
“…6 A) results from TPC pore blocking ability. Our data also suggest caution in attribution of the mechanistic basis of effects of SKF96365 in studies of Ca 2+ signaling [ 70 ]. PF-543 is a cell-permeant inhibitor of sphingosine kinase [ 49 ], application of which causes a dose-dependent increases in cellular sphingosine levels.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, Ned-19, a close analogue of NAADP, is likely to exert its inhibitory effect on TPCs in an indirect and complex manner, similar to NAADP itself. Nonetheless, the use of Ned-19 has, to a large extent, broadened our understanding of the roles of NAADP/TPCs in biological functions and diseases, especially over the past 5 years, in areas that include: cancer progression and metastasis [ 79 , 82 ], VEGF-induced angiogenesis [ 61 ], EBOV infection [ 39 ], proliferation and activation of T cells [ 83 ], autophagy of hepatocytes during liver injury [ 84 ], activation of endothelial progenitor cells [ 85 ], the noradrenaline-induced Ca 2+ response in smooth muscle cells [ 86 ], and the growth of Plasmodium , the causative agent of malaria [ 87 ].…”
Section: Pharmacological Modulators Of Tpcsmentioning
confidence: 99%
“…Particularly prominent is RyR1, as proposed by Guse and colleagues for Jurkat T cells (recently reviewed in Guse and Diercks 2018). However, RyR1 is not required for NAADP-evoked Ca 2+ release per se (Ruas et al 2015), and a role for acidic stores and TPCs have been demonstrated by others in T-cell activation (Davis et al 2012; Ali et al 2016). However, it remains possible that NAADP-binding proteins may associate with multiple ion channels under certain conditions (Galione and Petersen 2005; Gerasimenko et al 2015; Diercks et al 2018).…”
Section: Patch-clamping Lysosomesmentioning
confidence: 99%